Recyclable Adsorbents for Potash Brine Desalination Based on Silicate Powder: Application, Regeneration and Utilization - Akmaral B. Rakhym; Zarina Ye. Baranchiyeva; Aruzhan K. Kenessova; Bagashar B. Zhaksybai; Diana N. Dauzhanova; Yitzhak Mastai; Gulziya A. Seilkhanova (Colloids and Interfaces, 2023)
Silicate mineral powders (SMP) from weathered granite soil from Kazakhstan are proposed for the desalination of potash brines containing sodium, potassium and chloride ions. Batch adsorption experiments using acid-treated silicate (AS) achieved a Na+/K+/Cl− recovery of ~13/28/6 mg/g. An isothermal study best fitted the Freundlich and Dubinin–Radushkevich models for Na+ and K+/Cl−. The kinetic data were best modeled by pseudo-second-order kinetics for Na+/K+ and pseudo-first-order for Cl−. Thermodynamic calculations showed spontaneity under natural conditions. For Na+/K+, physisorption is accompanied by ion exchange. To study the possibility of sorbent reuse, several cycles of K+/Na+ adsorption–desorption were carried out under optimal conditions. AS selectively adsorbed potassium ions, maintaining a high effectiveness during five cycles providing K-form silicate fertilizers. Leachates of spent AS contain high concentrations of K/Na/Ca/Mg and other microelements essential for plants. Thus, SMP resolve two issues: the desalination of brine and the provision of fertilizer.